Modeling Polypharmacological Profiles by Affinity Fingerprinting - Peragovics, Agnes; Simon, Zoltan; Malnasi-Csizmadia, Andras; Bender, Andreas (Current Pharmaceutical Design, 2016)
Single target based approaches often proved to be unsuccessful in complex multigenic diseases such as cancer or schizophrenia. Multi-target drugs can be more efficacious in this regard by modulating multiple processes in the organism. According to the theory of polypharmacology, bioactive molecules possess characteristic interaction patterns that are responsible for their effects and side-effects and getting acquainted with this typical profile is increasingly desired to promote pharmaceutical research and development. There is a novel way of approaching polypharmacology that takes into account the interaction of molecules to a set of proteins that are not necessarily known biological targets of the compounds. Applying a carefully selected panel of proteins that can model the possible interactions a molecule can exert when administered to a human body, holds out a promise of biological activity prediction. This review aims to summarize a number of such bioactivity profiling-based approaches set up recently and present their application areas within the drug discovery field.
Keywords: Polypharmacology